The Reproducibility of Evolving Social Science Evidence and How It Shapes Equal Protection Jurisprudence - Azizi, Penney P. (2017)
In Brown v. Board of Education, the Supreme Court ruled that state laws establishing segregation in schools were unconstitutional, overturning Plessy v. Ferguson. In its decision, the Court discussed and cited to social science evidence, which garnered criticism from many legal scholars and ignited a debate as to whether the use of such evidence had a place in Equal Protection jurisprudence. Over thirty years later, in McClesky v. Kemp, the Court rejected the incorporation of social science data in its decision and, instead, applied the Intent Doctrine. Since McClesky, the Court has consistently upheld the use of the Intent Doctrine in Equal Protection cases. Although the Court still continues to use the Intent Doctrine, newer findings suggest that implicit biases within the human mind may also factor into discriminatory effect and should be taken into consideration without opening up the floodgates and disrupting the courts. While the Court has nevertheless been apprehensive about incorporating such studies into their rulings because these studies are not easily replicated, social science data still has its merits. This Note will argue that as of now, the Intent Doctrine does not provide a fair and equitable court system. This Note will advocate that the Court should consider alternatives to the Intent Doctrine that takes into consideration social science evidence, which may serve as a springboard to help the Court avoid unintended discrimination in its Equal Protection jurisprudence